Unlocking Legal Learning - Turner, Chris (Unlocking the Law, 2014)
Studying law can be a steep learning curve for anyone who is new to the subject. Unlocking Legal Learning is the essential guide for students who are about to embark on a period of legal study.Taking you from the basics of studying law and what to expect on your first day, Unlocking Legal Learning will show you how to:* use techniques of note-taking in lectures and seminars * access and understand legal materials and references* use legal reasoning* complete coursework and dissertation assignments* revise effectivelyUnlocking Legal Learning will ensure that you hit the ground running when you start your course and will remain an invaluable guide throughout your time of study.Further study support, including interactive multiple choice questions, is available on the free website www.unlockingthelaw.co.uk.Unlocking the Law is the groundbreaking series of textbooks with a unique approach to the study of law. Unlocking the Law textbooks have been written specifically to ensure that readers understand fully the concepts required and are able to apply them with confidence. All titles in the series follow the same format and include the same features so students can move easily from one subject to another